Isolated Proton Aurora Driven by EMIC Pc1 Wave: PWING, Swarm, and NOAA POES Multi‐Instrument Observations. Issue 18 (10th September 2021) - Kim, Hyangpyo; Shiokawa, Kazuo; Park, Jaeheung; Miyoshi, Yoshizumi; Miyashita, Yukinaga; Stolle, Claudia; Connor, Hyunju Kim; Hwang, Junga; Buchert, Stephan; Kwon, Hyuck‐Jin; Nakamura, Satoko; Nakamura, Kohki; et al.
Abstract: We report the concurrent observations of F‐region plasma changes and field‐aligned currents (FACs) above isolated proton auroras (IPAs) associated with electromagnetic ion cyclotron Pc1 waves. Key events on March 19, 2020 and September 12, 2018 show that ground magnetometers and all‐sky imagers detected concurrent Pc1 wave and IPA, during which NOAA POES observed precipitating energetic protons. In the ionospheric F‐layer above the IPA zone, the Swarm satellites observed transverse Pc1 waves, which span wider latitudes than IPA. Around IPA, Swarm also detected the bipolar FAC and localized plasma density enhancement, which is occasionally surrounded by wide/shallow depletion. This indicates that wave‐induced proton precipitation contributes to the energy transfer from the magnetosphere to the ionosphere. Plain Language Summary: Electromagnetic ion cyclotron (EMIC) wave is known to precipitate energetic protons into the Earth's atmosphere via pitch angle scattering. Observations from ground‐based magnetometers, all‐sky imagers, and low Earth orbit satellites have shown that the precipitating protons scattered by EMIC waves can generate proton aurora isolated at a subauroral latitude. This kind of aurora is called isolated proton aurora (IPA, or detached proton auroral arc). In the present paper, we report the observations of concurrent Pc1 wave, proton precipitation, ionospheric perturbation, field‐aligned currents (FACs), and IPA using data from ground instruments, and from the Swarm and NOAA POES satellites. The observations show that the latitudinal (L‐shell) size of EMIC wave at Swarm altitude is larger than that of the IPA. We also investigated the effects of proton precipitation on the ionospheric F‐layer from Swarm satellite data, and found localized plasma density enhancement and FAC near the central IPA region. Our results demonstrate that the EMIC‐driven proton precipitation contributes to the energy transfer from the magnetosphere to the ionosphere. Key Points: We report the concurrent observations of Pc1 wave, proton precipitation, ionospheric perturbation, field‐aligned current, and isolated proton aurora (IPA) Pc1 waves over the ionospheric F‐layer and IPA over the E‐layer show different latitudinal widths Proton precipitation can cause localized plasma density enhancement, which is occasionally surrounded by wide/shallow density depletion